2020
DOI: 10.4317/jced.56863
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cytotoxic and antimicrobial activities of two components of Cymbopogon citratus essential oil

Abstract: Background There is a continuing search for compuounds to improve the chemical plaque inhibitory action of oral hygiene products. Although the antibacterial effects of chlorhexidine (CHX) and essential oils components, citral/myrcene, have been described, there is contradictory information regarding their cytotoxic effects in host tissues. This study aimed to evaluate the cytotoxic activity of the major components of the oil C. citratus , citral and myrcene on human peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Benzyl alcohol is mainly used as a fragrance and preservative [ 114 , 115 ] and only its derivative (2,4-dichlorobenzyl alcohol) is used as a mild oral and pharyngeal antiseptic. Limonene [ 99 , 116 , 117 ], linalool [ 99 , 117 ], citral [ 118 ] and cinnamal (cinnamaldehyde) [ 119 ] exhibit a non-negligible activity against oral pathogenic microorganisms. Geraniol [ 120 ] and anethole [ 121 ] also show some antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Benzyl alcohol is mainly used as a fragrance and preservative [ 114 , 115 ] and only its derivative (2,4-dichlorobenzyl alcohol) is used as a mild oral and pharyngeal antiseptic. Limonene [ 99 , 116 , 117 ], linalool [ 99 , 117 ], citral [ 118 ] and cinnamal (cinnamaldehyde) [ 119 ] exhibit a non-negligible activity against oral pathogenic microorganisms. Geraniol [ 120 ] and anethole [ 121 ] also show some antimicrobial properties.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation conducted by Oukerrou et al found that AC EO exerted a dose-dependent cytotoxic effect on P815, MCF7, and VERO tumor cell lines, with IC 50 ranging from 6.60 to 79.63 μg/mL [ 27 ]. Moreover, Chaves-Quirós found that Citral, which is a major component in the current study, has a cytotoxic effect against human periodontal ligament fibroblast cancer cells and exhibited bacteriostatic/bactericidal effects to Streptococcus mutans, Lactobacillus rhamnosus, and Enterococcus faecalis strains [ 35 ].…”
Section: Discussionmentioning
confidence: 97%
“…for the observed antibacterial activity). Antibiofilm effect could also be attributed to citrals as a few recent studies confirmed their high antibacterial and antibiofilm activity against numerous bacterial species, including E. faecalis [51][52][53][54]. The recent study of Gao et al [45] demonstrating that they possess remarkable potential to diminish all components of biofilm matrix (nucleic acid, proteins and carbohydrates) of combined pathogens S. aureus and Candida spp., additionally strengthen this claim.…”
Section: Discussionmentioning
confidence: 98%